Les états de femme et la construction de la féminité dans la fiction durassienne - Ledwina, Anna (Romanica Silesiana)
The Condition of Woman and Modelling of Femininity in the Novels of Marguerite Duras Marguerite Duras’s writings are a part of a broadly defined discourse on the condition and role of women in a patriarchal society. The author criticises the fact that women are excluded from the public sphere and deprived of the right to self-determination and choice. Consequently, her heroines rebel against the existing mores and are determined to break with their current existence. By shaking off motherly supervision, the protagonists are capable of achieving their own aspirations and of transgressing to independence even against public opinion. The hidden and suppressed longings of the heroines manifest Duras’s own experiences. Through an image of a strong and courageous woman, the author shows a representative of her own gender — a multi-dimensional character, capable of self-discovery, defying reality, and expressing her own sexuality. The search for love, one of the leitmotifs of Duras’s works, reflects the author’s desire to discover and name her own female identity. Key words: woman, identity, freedom, desire, rebellion, transgression.